Apocalyptic and Merkavah mysticism - Gruenwald, Ithamar. (Ancient Judaism and Early Christianity, 2014)
This is a new and revised edition of the book first published 1980. It contains new introductory and concluding chapters as well as a Bibliography and updated Index. Furthermore, substantial corrections, updates, and changes have been made in the original text. The changes concern matters of language and style, they nuance the line of argumentation, and they update the discussion of major issues. The new chapters fill several scholarly gaps that have opened since the initial publication of this book in 1980. The new Introductory Chapter explores new venues and issues in the study and assessment of the Hekhalot literature and relevant passages in apocalyptic literature, and this in light of epistemological and ontological considerations. The Concluding Chapter discusses the ritual praxis of the experience of the Hekhalot mystics and its affitnity to magic, and this in terms of new approaches to ritual theory.